THE ROLE OF INDIVIDUAL PSYCHOLOGICAL DIFFERENCES IN THE PROFESSIONAL SELF-DETERMINATION OF YOUTH - Zasiekin, Artur (Personality and environmental issues, 2025)
The article analyzes the influence of individual psychological differences on the process of professional self-determination of young people. The role of personal characteristics, motivational attitudes, thinking styles and the level of emotional self-regulation in choosing a professional trajectory is revealed. Factors that facilitate or complicate career decision-making in conditions of social instability and transformation of the educational space are identified. The feasibility of an individualized approach to professional counseling is substantiated, which takes into account the psychological specifics of young people and contributes to the successful realization of personal potential.The article reveals the importance of individual psychological differences as a key factor in the process of professional self-determination of young people. The author emphasizes that career decisions are formed not only under the influence of external conditions (social, economic), but also through the prism of internal personal characteristics that determine the perception of professional reality and adaptation mechanisms. Professional self-determination is considered as a multi-component process that includes assessing one’s own potential, setting goals, choosing an educational or career trajectory, and adapting to changes. The feasibility of using an individualized approach in career guidance activities, educational practices, and advisory programs is substantiated, especially in conditions of social instability and labor market transformations. Such an approach contributes to the formation of professional identity, self-realization strategies, and the development of flexible thinking.The main models of professional counseling (holistic, narrative, cognitive-behavioral, coaching, and adaptive) are revealed, which demonstrate strategic flexibility in supporting young people, taking into account psychological diversity, motivational attitudes, and emotional readiness for self-determination. Such models are not only tools for career guidance, but also means of developing self-realization strategies in a dynamic socio-cultural space.